Characterization of Comorbidities Limiting the Recruitment of Patients in Early Phase Clinical Trials. (9th November 2018) - Duma, Narjust; Kothadia, Sejal M.; Azam, Tariq U.; Yadav, Siddhartha; Paludo, Jonas; Vera Aguilera, Jesus; Gonzalez Velez, Miguel; Halfdanarson, Thorvardur Ragnar; Molina, Julian R.; Hubbard, Joleen M.; Go, Ronald S.; Mansfield, Aaron S.; et al.
Abstract: Background: Early phase clinical trials evaluate the safety and efficacy of new treatments. The exclusion/inclusion criteria in these trials are usually rigorous and may exclude many patients seen in clinical practice. Our objective was to study the comorbidities limiting the participation of patients with breast, colorectal, or lung cancer in clinical trials. Materials and Methods: We queried ClinicalTrials.gov on December 31, 2016. We reviewed the eligibility criteria of 1, 103 trials. Logistic regression analyses were completed, and exclusion was studied as a binary variable. Results: Out of 1, 103 trials, 70 trials (6%) excluded patients >75 years of age, and 45% made no reference to age. Eighty‐six percent of trials placed restrictions on patients with history of prior malignancies. Regarding central nervous system (CNS) metastasis, 416 trials (38%) excluded all patients with CNS metastasis, and 373 (34%) only allowed asymptomatic CNS metastasis. Regarding chronic viral infections, 347 trials (31%) excluded all patients with human immunodeficiency virus, and 228 trials (21%) excluded all patients with hepatitis B or C infection. On univariate analysis, chemotherapy trials were more likely to exclude patients with CNS metastasis and history of other malignancies than targeted therapy trials. Multivariate analysis demonstrated that industry‐sponsored trials had higher odds of excluding patients with compromised liver function. Conclusion: Many clinical trials excluded large segments of the population of patients with cancer. Frequent exclusion criteria included patients with CNS metastasis, history of prior malignancies, and chronic viral infections. The criteria for participation in some clinical trials may be overly restrictive and limit enrollment. Implications for Practice: The results of this study revealed that most early phase clinic trials contain strict exclusion criteria, potentially excluding the patients who may be more likely to represent the population treated in clinical settings, leaving patients susceptible to unintended harm from inappropriate generalization of trial results. Careful liberalization of the inclusion/exclusion criteria in clinical trials will allow investigators to understand the benefits and drawbacks of the experimental drug for a broader population, and possibly improve recruitment of patients with cancer into clinical trials. Abstract : Although the number of clinical trials registered annually has increased, inclusion and exclusion criteria limit the number of patients eligible for trial participation. This study aimed to identify comorbidities and other exclusion criteria that have limited the recruitment of patients with breast, colorectal, and lung cancers into early phase clinical trials.